Creating Italian Switzerland: Canton of Ticino in 19th Century - T. P. Nesterova (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The history of the Swiss Canton of Ticino in the 19th century is examined. A review of the main historical events that had an important influence on the development of the Canton is made. In particular, the importance of “Act of Mediation” of Napoleon Bonaparte is noted, as the history of the Canton as an independent territorial and political unit in Switzerland began from the time of its signing. The characteristic of Canton political structure, its principal political forces, the liberals and the conservatives, is given. It is shown that the antagonism between them has remained unchanged throughout these periods. It is emphasized that the main task of the Canton government in the period under review was the creation of a unite space with a single management structure and laws. Socio-economic changes are analyzed aimed at achieving the goals listed above. A review of the basic events in the history of Canton is made. The role of certain political figures that influenced the development of the Canton in the 19th century is analyzed.